Fixed extrathoracic obstruction masquerading as poorly controlled asthma - Crain, Nikhil A; Thompson, Jennifer L; Cristiano, Leslie M (Indian Journal of Case Reports, 2025)
We present the misdiagnosis of asthma in a 27-year-old female with a subsequent diagnosis of fixed extrathoracic obstruction supported by pulmonary function testing in the outpatient asthma clinic. Subsequent otolaryngology evaluation demonstrated arytenoid hooding and suspected upper tracheal narrowing on nasolaryngoscopy. Intraoperative airway evaluation confirmed advanced subglottic stenosis (SGS), which required surgical incision and balloon dilation. Tracheostomy decannulation as a toddler was the suspected etiology of acquired SGS.